2018
DOI: 10.1161/jaha.117.006479
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Lectin‐Like Oxidized Low‐Density Lipoprotein Receptor‐1 in Ischemic Stroke and Transient Ischemic Attack

Abstract: BackgroundSoluble lectin‐like oxidized low‐density lipoprotein receptor‐1 (sLOX‐1) has been shown to be increased in patients with acute ischemic stroke. Here, we evaluated plasma sLOX‐1 levels and vascular carotid plaque LOX‐1 (ie, OLR1) gene expression in patients with ischemic stroke and transient ischemic attack (TIA) with particular focus on their relation to time since symptom onset.Methods and ResultsPlasma sLOX‐1 (n=232) and carotid plaque OLR1 gene expression (n=146) were evaluated in patients who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…Importantly, LOX‐1 has a positive correlation with thrombolysis in myocardial infarction score and heart failure. In agreement with these findings, sLOX‐1 levels and LOX‐1 gene expression are elevated in carotid atherosclerotic plaques from human patients with ischemic stroke . Hence, circulating sLOX‐1 could be a useful biomarker to predict major cardiovascular events, as well as used for screening of high‐risk individuals and the management of ACS patients .…”
Section: Slox‐1 As a Useful Biomarker Of Cardiovascular And Sickle Cesupporting
confidence: 70%
See 2 more Smart Citations
“…Importantly, LOX‐1 has a positive correlation with thrombolysis in myocardial infarction score and heart failure. In agreement with these findings, sLOX‐1 levels and LOX‐1 gene expression are elevated in carotid atherosclerotic plaques from human patients with ischemic stroke . Hence, circulating sLOX‐1 could be a useful biomarker to predict major cardiovascular events, as well as used for screening of high‐risk individuals and the management of ACS patients .…”
Section: Slox‐1 As a Useful Biomarker Of Cardiovascular And Sickle Cesupporting
confidence: 70%
“…LOX‐1 also inhibits macrophage migration and promotes foam cell formation induced by various proatherogenic treatments . A recent study has shown that LOX‐1 colocalizes with macrophages in human carotid plaques, indicating the potential role of LOX‐1 in regulating foam cell formation and plaque vulnerability in atherosclerosis development in humans.…”
Section: Cellular and Molecular Mechanisms Of Lox‐1 In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…73 The serum-soluble form of LOX-1 (sLOX-1), the extracellular portion of LOX-1 produced by proteolytic shedding of the receptor, reflects membrane-bound intact receptor levels and is elevated in acute coronary syndrome (ACS), 74 stable coronary artery disease 75 and stroke. 76 The association of LOX-1 activation and acute inflammatory conditions raises the possibility that LOX-1 is also activated and may contribute to COVID-19 complications. In fact, recent clinical data suggest that SARS-CoV-2 may cause a pediatric multisystem inflammatory syndrome reminiscent of Kawasaki Disease (KD) in children.…”
Section: And Scavenger Receptors In Covid-19mentioning
confidence: 99%
“…Recently, inflammatory HDL from SLE patients was shown to reduce the nuclear co-localization of ATF3, an anti-inflammatory transcription factor, through the LOX-1 receptor, making primary human monocyte-derived macrophages prone to inflammatory cytokine secretion [24]. In human disease, elevated levels of cleaved soluble LOX-1 (sLOX-1) have been reported in patients with acute coronary syndrome [25,26], systolic heart failure [27], ischemic stroke [28], and psoriasis [29].…”
Section: Introductionmentioning
confidence: 99%